Edukasi Pencegahan Dini Stunting pada Remaja Menuju Zero Stunting Tahun 2025 - Sandra Dewi; Jufrika Gusni; Debby Silvia Dewi; Maidawillis Maidawillis; Mike Asmaria (Jurnal Medika: Medika, 2026)
The rapid development of food and beverage products encourages adolescents to choose low-nutrient foods, thus increasing the risk of nutritional imbalance and stunting. Lubuk Alung still has a stunting incidence of 2.4%. MAN 1 Padang Pariaman, one of the schools located in Lubuk Alung District. The purpose of the community service is to improve adolescents' knowledge and skills in preventing stunting. The service method is through education and demonstration of nutritional actions. The results of the activity showed an increase in participants' knowledge regarding balanced nutrition and stunting prevention, as well as their ability to practically prepare healthy menus. This activity emphasizes the important role of schools in supporting stunting prevention efforts and fostering healthy lifestyle behaviors among adolescents, as part of the Zero Stunting program target